COVID-19 infection, inception and immunity: Observations and recommendations in the light of vitamin D?. Issue 4 (April 2021) - Dixit, Vivek; Garg, Bhavuk; Mehta, Nishank; Pegrum, James; Dhanwal, Dinesh
Abstract: Responsive immunity plays an important role fighting against infections. Worldwide, Vitamin D deficiency is a major concern not only for musculoskeletal health but also affecting the immunity status in population. Amidst COVID-19 pandemic, it is imperative to establish the role of vitamin D in destruction of pathogens. Vitamin D awareness program at school level might be an effective health governance policy to educate populations for the importance of vitamin D in overall health.